Belenggu Patriarki pada Peran Laki-Laki Bangsawan Jawa dalam Film Kartini Karya Hanung Bramantyo - Marsya, Ulmi; Faladhin, Johan (POPULIKA, 2019)
The struggle of Raden Ayu Kartini to gain freedom for Javanese women who were hindered by the great walls of culture and tradition, often associated with patriarchal culture which was said to give more privileges to men than women. But in fact the privileges possessed by men instead of giving freedom, it also binds his mind to the true roles and behavior of men who have been established in the patriarchal culture itself.